PROFIL KARAKTERISTIK PETERNAK KAMBING RAKYAT DI KECAMATAN INSANA UTARA (Studi Kasus Di Desa Wini, Oesoko, Oekolo Kecamatan Insana Utara Kabupaten Timor Tengah Utara) - Beyleto, Veronika Yuneriati; Thaal, Maria Elisa; Sahala, Josua; Simamora, Ture; Pasi, Maria Selfiana (Innovative: Journal Of Social Science Research, 2025)
This study aims to determine the characteristics of goat farmers in North Insana District, North Central Timor Regency, This research was conducted in July-September 2024 in Wini, Oekolo and Oesoko villages, North Insana District, North Central Timor Regency. This study uses a survey method by applying quantitative descriptive analysis techniques to collect secondary data and primary data from respondents. This study applied the purposive sampling method and the research variables were as follows. characteristics based on age, gender, formal education, non-formal education, occupation, ownership scale, experience of livestock farming, cosmopolitan level, and motivation for livestock farming. The results of this study are profiles of the characteristics of goat farmers (case study in Winniekolo village, North Insana District, North Central Timor Regency) based on the age of most farmers 21-35 years old 90.1%, gender 69.7%, male level of formal education 56.3%, elementary school level of non-formal education 95, 1% have never participated in training, employment of 58.5% of long-term farmers raising livestock 45.1% 0-5 years, livestock ownership 68.3% have 1-10 livestock, Cosmopolitan level 57% leave the village 0-5 times per month, watch TV 100% 0-5 times, listen to the radio 100% 0-5 times, meet practitioners 100% have never met, motivation to raise livestock 100% increase income.